Flexible transparent aqueous zinc ion battery polyaniline / vanadium oxide composite positive pole piece and preparation method thereof
By depositing vanadium oxide and polyaniline layer by two-step electrodeposition method on the gold grid/PET surface, a flexible transparent water-based zinc ion battery polyaniline/vanadium oxide composite positive electrode sheet was prepared, which solved the problem that flexible transparent zinc ion battery could not achieve transparent effect in the prior art, and achieved a high-performance flexible transparent energy storage battery.
Patent Information
- Application Number
- CN202510089875.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-21
AI Technical Summary
Existing flexible transparent zinc ion batteries cannot achieve transparent effects and cannot meet the transparency requirements of flexible electronic products and wearable devices.
A two-step electrodeposition method was used to deposit vanadium oxide and polyaniline layer on the surface of the gold grid/PET to prepare a flexible transparent aqueous zinc ion battery polyaniline/vanadium oxide composite positive electrode sheet.
A flexible transparent aqueous zinc ion battery with high specific capacity, high cycle stability, high bending resistance and light transmittance is achieved, suitable for energy storage components of wearable mobile devices.
Smart Images

Figure CN119920814A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aqueous zinc ion batteries, and in particular relates to a flexible transparent aqueous zinc ion battery polyaniline / vanadium oxide composite positive electrode plate and a preparation method thereof. Background Art
[0002] In recent years, flexible transparent electronic products such as flexible transparent touch screens, smart wristbands, wearable sensors, electronic skin, and implantable medical devices have developed rapidly. Flexible transparent energy storage electronic devices can provide energy supply for flexible electronic systems and are one of the core components of flexible electronic systems. Flexible transparent energy storage electronic devices need to have excellent flexibility and transparency while maintaining electrochemical properties. This requires that the positive electrode, negative electrode, diaphragm, electrolyte, current collector and packaging materials that make up the device need to have good light transmittance and mechanical flexibility. Supercapacitors have a simple structure, high reliability and good safety, but their low energy density restricts their application in flexible transparent electronic products. Although lithium-ion batteries have excellent energy density, there are still great challenges in the construction of flexible transparent devices. Therefore, there is an urgent need to develop new energy storage devices with high flexibility, high transparency, high energy density and high safety.
[0003] Rechargeable zinc-ion batteries have the advantages of high safety, high energy density, abundant resources and low cost, and are a new type of energy storage device with great market competitiveness. In recent years, with the sharp increase in demand for flexible electronic devices, the research and development of flexible zinc-ion battery devices has developed rapidly, and a variety of flexible zinc-ion battery materials and devices have been developed. However, since flexible transparent metal electrodes are generally manufactured using vacuum coating technology, zinc has a low melting point and poor hardness, making flexible transparent zinc electrodes is extremely challenging.
[0004] At present, manganese-based oxides, Prussian blue analogs and vanadium-based oxides are actively explored as positive electrode materials for aqueous zinc-ion batteries. However, in traditional alkaline electroplating solutions, positive electrode materials are usually affected by dendrite growth and byproduct problems, resulting in serious irreversibility, and most of them are troubled by limited capacity or poor cycle stability. Invention patent CN110190344A discloses a flexible aqueous zinc-ion battery, in which the current collecting layer includes a breathable layer and a substrate layer, and the substrate layer has at least one opening. The open-pore structure of the breathable layer and the substrate layer improves the cycle performance of the battery, and the assembled aqueous zinc-ion battery has certain bending properties, but the battery cannot achieve a transparent effect and cannot meet the transparency requirements of flexible electronic products and wearable devices.
[0005] To this end, a flexible transparent aqueous zinc ion battery polyaniline / vanadium oxide composite positive electrode sheet and a preparation method thereof are proposed. Summary of the invention
[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a flexible transparent aqueous zinc ion battery polyaniline / vanadium oxide composite positive electrode plate and a preparation method thereof, thereby solving the problems in the prior art.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] A method for preparing a flexible transparent aqueous zinc ion battery polyaniline / vanadium oxide composite positive electrode sheet comprises the following steps:
[0009] S1, using a vanadyl sulfate aqueous solution as an electroplating solution, using a gold grid / PET as a working electrode, and a platinum sheet as a counter electrode to construct a two-electrode structure, and using a constant voltage electrochemical deposition method to deposit a vanadium oxide layer on the surface of the gold grid / PET to prepare vanadium oxide / gold grid / PET;
[0010] S2, adding sulfuric acid and aniline into deionized water to prepare an electroplating solution, constructing a three-electrode structure with vanadium oxide / gold grid / PET as a working electrode, a platinum electrode as a counter electrode, and a saturated calomel electrode as a reference electrode, and using a constant voltage electrochemical deposition method to deposit a polyaniline layer on the surface of vanadium oxide / gold grid / PET to obtain a composite positive electrode sheet.
[0011] Furthermore, the sheet resistance of the gold grid / PET current collector is 1-2Ω / sq, and the light transmittance is 80-90%.
[0012] Furthermore, the concentration of the vanadyl sulfate aqueous solution is 0.05-0.2 mol / L.
[0013] Furthermore, in S1, during the electrochemical deposition process, the two-electrode system is stirred at a constant temperature of 50-80°C and a stirring condition of 300r / min-1000r / min.
[0014] Furthermore, in S1, the deposition potential range of the constant voltage electrochemical deposition method is 0.8-2.0 V, and the deposition time is 10-25 min.
[0015] Furthermore, in S2, in the prepared electroplating solution, the concentration of sulfuric acid is 0.5-2 mol / L, and the concentration of aniline is 0.2-1 mol / L.
[0016] Furthermore, in S2, the deposition potential range of the constant voltage electrochemical deposition method is 0.55-0.95 V, and the deposition time is 30-120 s.
[0017] The flexible transparent aqueous zinc ion battery polyaniline / vanadium oxide composite positive electrode plate is prepared by the above-mentioned preparation method.
[0018] The above-mentioned flexible transparent aqueous zinc ion battery polyaniline / vanadium oxide composite positive electrode plate is used in the preparation of aqueous zinc ion batteries.
[0019] An aqueous zinc ion battery comprises the above-mentioned flexible transparent aqueous zinc ion battery polyaniline / vanadium oxide composite positive electrode plate.
[0020] Beneficial effects of the present invention:
[0021] 1. The present invention adopts a simple and easy two-step electrodeposition method to deposit vanadium oxide and polyaniline layer on the surface of gold grid / PET, and prepares a flexible and transparent aqueous zinc ion battery polyaniline / vanadium oxide / gold grid / PET composite positive electrode with high specific capacity, high cycle stability, high bending resistance and transmittance. The vanadium oxide deposited on the gold grid substrate has good layered structure characteristics, which is Zn 2+ Rapid intercalation and deintercalation between vanadium oxide layers provides open channels.
[0022] 2. The structural water molecules of the present invention can also play a role in charge shielding, reducing the electrostatic interaction between the main framework and the cations. Continuing to grow polyaniline on the vanadium oxide substrate can improve the conductivity and light transmittance of the material through the composite with polyaniline, and the synergistic effect of polyaniline and vanadium oxide can improve the energy storage performance of the material.
[0023] 3. The aqueous zinc ion battery polyaniline / vanadium oxide composite positive electrode plate of the present invention exhibits excellent specific capacity, good mechanical flexibility, good transparency, and stable cycle performance. As an energy storage component for wearable mobile devices, it has good application potential and prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0025] Figure 1 These are optical microscope images and SEM images of the composite positive electrode sheet of the present invention;
[0026] Figure 2 This is an optical photograph of a flexible transparent aqueous zinc ion battery assembled with a composite positive electrode plate of the present invention;
[0027] Figure 3 It is a charge and discharge curve diagram of the flexible transparent aqueous zinc ion battery assembled with the composite positive electrode plate of the present invention. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] A method for preparing a flexible transparent aqueous zinc ion battery polyaniline / vanadium oxide composite positive electrode sheet comprises the following steps:
[0030] (1) Vanadyl sulfate powder is added to deionized water to prepare a vanadyl sulfate aqueous solution as an electroplating solution; a gold grid / PET is used as a working electrode and a platinum sheet is used as a counter electrode to construct a two-electrode structure, and a vanadium oxide layer is deposited on the surface of the gold grid / PET by a constant voltage electrochemical deposition method to prepare a vanadium oxide / gold grid / PET.
[0031] (2) adding sulfuric acid and aniline into deionized water to prepare a mixed solution containing sulfuric acid and aniline as an electroplating solution, using the vanadium oxide / gold grid / PET prepared in step (1) as a working electrode, a platinum electrode as a counter electrode, and a saturated calomel electrode as a reference electrode to construct a three-electrode structure, and using a constant voltage electrochemical deposition method to deposit a polyaniline layer on the surface of the vanadium oxide / gold grid / PET to prepare a flexible transparent polyaniline / vanadium oxide / gold grid / PET composite positive electrode sheet.
[0032] The gold grid / PET used in step (1) has a square resistance of 1-2Ω / sq and a light transmittance of 80-90%.
[0033] The concentration of the vanadyl sulfate aqueous solution in step (1) is 0.05-0.2 mol / L.
[0034] In step (1), during the electrochemical deposition process, the two-electrode system is stirred at a constant temperature of 50-80°C and a stirring condition of 300r / min-1000r / min; the deposition potential range of the constant voltage electrochemical deposition method is 0.8-2.0V, and the deposition time is 10-25min.
[0035] In step (2), the concentration of sulfuric acid in the mixed solution is 0.5-2 mol / L, and the concentration of aniline is 0.2-1 mol / L.
[0036] In step (2), the deposition potential range of the constant voltage electrochemical deposition method is 0.55-0.95 V, and the deposition time is 30-120 s.
[0037] The following examples and comparative examples are used to specifically illustrate the preparation process of the composite positive electrode sheet, wherein the sources of the raw materials used in the examples and comparative examples are as follows:
[0038] The gold grid / PET was homemade, and a highly connected gold wire grid was prepared on a PET substrate using a crack template method and a vacuum deposition process to obtain a gold grid / PET. Specifically, acrylic resin and ethanol were stirred and mixed in a volume ratio of 2:1 to obtain a mixed solution; the mixed solution was scraped onto the surface of the plasma-cleaned PET substrate; the sample was transferred to a vacuum drying oven and dried at 80°C for 30 minutes to obtain an acrylic resin crack network template sample; the sample was placed in a high vacuum metal evaporation coating system with a vacuum degree of 2×10 -4 Pa, vacuum deposited an 18 nm gold film at a substrate temperature of 100°C; immersed the sample in acetic acid and ultrasonically treated for 1 min to remove the acrylic resin template layer; took out the sample, washed it with ultrapure water and ethanol, and vacuum dried it at 80°C for 1 h to obtain a gold grid / PET.
[0039] Acrylic resin: Manufacturer: Sinopharm Chemical Reagent Co., Ltd.; Specification: AR;
[0040] Ethanol: Manufacturer: Sinopharm Chemical Reagent Co., Ltd.; Specification: 99.9%;
[0041] Acetic acid: Manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd.; Specification: AR;
[0042] Gold particles: Manufacturer: Sinopharm Chemical Reagent Co., Ltd.; Specification: 99.99%;
[0043] Vanadyl sulfate: Manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd.; Specification: AR; Item No.: V431627-25g;
[0044] Aniline: Manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd.; Specification: AR; Item No.: A112120-500ml;
[0045] Sulfuric acid: Manufacturer: Sinopharm Chemical Reagent Co., Ltd.; Specification: AR; Sinopharm code: 10021661;
[0046] ITO / PET: Manufacturer: Luoyang Tengchang Xukun Biotechnology Co., Ltd.; Specification: square resistance 7 ohms.
[0047] Example 1
[0048] (1) 3.26 g of vanadyl sulfate was added to 200 mL of deionized water to prepare an electroplating solution, a gold grid / PET (2.5 cm×2.5 cm) was used as a working electrode, a platinum sheet was used as a counter electrode, and a saturated calomel electrode was used as a reference electrode. The solution was heated at a constant temperature in a water bath at 50°C, and the stirring condition was 300 r / min. Constant voltage electrochemical deposition was performed, the deposition potential was 1.8 V, and the deposition time was 15 min. The obtained samples were then washed with deionized water in turn and dried in an oven at 50°C for 2 h.
[0049] (2) Take 200 mL of a mixed solution of 1 mol / L dilute sulfuric acid and 0.5 mol / L polyaniline, use the sample prepared in step (1) as the working electrode, the platinum electrode as the counter electrode, and the saturated calomel electrode as the reference electrode, and perform constant voltage electrochemical deposition at room temperature with a deposition potential of 0.75 V and a deposition time of 60 s to prepare the sample. Then, the obtained sample is washed with deionized water and anhydrous ethanol in turn, and dried in an oven at 50°C for 2 h to obtain a polyaniline / vanadium oxide / gold grid / PET composite positive electrode sheet with an area of 2.5 cm×2.5 cm.
[0050] Figure 1 (a) and (b) are optical microscope and SEM images of the prepared flexible transparent aqueous zinc ion battery polyaniline / vanadium oxide composite positive electrode; it can be seen from Figures a and b that the polyaniline / vanadium oxide composite film layer grows uniformly on the gold grid / PET current collector. In addition, it can be seen from Figure b that the surface of the polyaniline / vanadium oxide composite film is relatively rough, which is conducive to reducing the interface impedance and improving the storage capacity of zinc ions.
[0051] Example 2
[0052] (1) 3.26 g of vanadyl sulfate was added to 200 mL of deionized water to prepare the electroplating solution, a gold grid / PET (2.5 cm×2.5 cm) was used as the working electrode, a platinum sheet was used as the counter electrode, and a saturated calomel electrode was used as the reference electrode. The solution was heated at a constant temperature in a water bath at 50°C, and the stirring condition was 300 r / min. Constant voltage electrochemical deposition was performed, the deposition potential was 1.8 V, and the deposition time was 10 min. The obtained samples were then washed with deionized water in turn and dried in an oven at 50°C for 2 h.
[0053] (2) Take 200 mL of a mixed solution of 1 mol / L dilute sulfuric acid and 0.5 mol / L polyaniline, use the sample prepared in step (1) as the working electrode, the platinum electrode as the counter electrode, and the saturated calomel electrode as the reference electrode, and perform constant voltage electrochemical deposition at room temperature with a deposition potential of 0.75 V and a deposition time of 60 s to prepare the sample. Then, the obtained sample is washed with deionized water and anhydrous ethanol in turn, and dried in an oven at 50°C for 2 h to obtain a polyaniline / vanadium oxide / gold grid / PET composite positive electrode sheet with an area of 2.5 cm×2.5 cm.
[0054] Example 3
[0055] (1) 3.26 g of vanadyl sulfate was added to 200 mL of deionized water to prepare an electroplating solution, a gold grid / PET (2.5 cm×2.5 cm) was used as a working electrode, a platinum sheet was used as a counter electrode, and a saturated calomel electrode was used as a reference electrode. The solution was heated at a constant temperature in a water bath at 50°C, and the stirring condition was 300 r / min. Constant voltage electrochemical deposition was performed, the deposition potential was 1.8 V, and the deposition time was 20 min. The obtained samples were then washed with deionized water in turn and dried in an oven at 50°C for 2 h.
[0056] (2) Take 200 mL of a mixed solution of 1 mol / L dilute sulfuric acid and 0.5 mol / L polyaniline, use the sample prepared in step (1) as the working electrode, the platinum electrode as the counter electrode, and the saturated calomel electrode as the reference electrode, and perform constant voltage electrochemical deposition at room temperature with a deposition potential of 0.75 V and a deposition time of 60 s to prepare the sample. Then, the obtained sample is washed with deionized water and anhydrous ethanol in turn, and dried in an oven at 50°C for 2 h to obtain a polyaniline / vanadium oxide / gold grid / PET composite positive electrode sheet with an area of 2.5 cm×2.5 cm.
[0057] Example 4
[0058] (1) 3.26 g of vanadyl sulfate was added to 200 mL of deionized water to prepare the electroplating solution, a gold grid / PET (2.5 cm × 2.5 cm) was used as the working electrode, a platinum sheet was used as the counter electrode, and a saturated calomel electrode was used as the reference electrode. The solution was heated at a constant temperature in a water bath at 50°C, and the stirring condition was 300 r / min. Constant voltage electrochemical deposition was performed, the deposition potential was 1.8 V, and the deposition time was 25 min. The obtained samples were then washed with deionized water in turn and dried in an oven at 50°C for 2 h.
[0059] (2) Take 200 mL of a mixed solution of 1 mol / L dilute sulfuric acid and 0.5 mol / L polyaniline, use the sample prepared in step (1) as the working electrode, the platinum electrode as the counter electrode, and the saturated calomel electrode as the reference electrode, and perform constant voltage electrochemical deposition at room temperature with a deposition potential of 0.75 V and a deposition time of 60 s to prepare the sample. Then, the obtained sample is washed with deionized water and anhydrous ethanol in turn, and dried in an oven at 50°C for 2 h to obtain a polyaniline / vanadium oxide / gold grid / PET composite positive electrode sheet with an area of 2.5 cm×2.5 cm.
[0060] Example 5
[0061] (1) 3.26 g of vanadyl sulfate was added to 200 mL of deionized water to prepare an electroplating solution, a gold grid / PET (2.5 cm×2.5 cm) was used as a working electrode, a platinum sheet was used as a counter electrode, and a saturated calomel electrode was used as a reference electrode. The solution was heated at a constant temperature in a water bath at 50°C, and the stirring condition was 300 r / min. Constant voltage electrochemical deposition was performed, the deposition potential was 1.8 V, and the deposition time was 15 min. The obtained samples were then washed with deionized water in turn and dried in an oven at 50°C for 2 h.
[0062] (2) Take 200 mL of a mixed solution of 1 mol / L dilute sulfuric acid and 0.5 mol / L polyaniline, use the sample prepared in step (1) as the working electrode, the platinum electrode as the counter electrode, and the saturated calomel electrode as the reference electrode, and perform constant voltage electrochemical deposition at room temperature with a deposition potential of 0.75 V and a deposition time of 30 s to prepare the sample. Then, the obtained sample is washed with deionized water and anhydrous ethanol in turn, and dried in an oven at 50°C for 2 h to obtain a polyaniline / vanadium oxide / gold grid / PET composite positive electrode sheet with an area of 2.5 cm×2.5 cm.
[0063] Example 6
[0064] (1) 3.26 g of vanadyl sulfate was added to 200 mL of deionized water to prepare an electroplating solution, a gold grid / PET (2.5 cm×2.5 cm) was used as a working electrode, a platinum sheet was used as a counter electrode, and a saturated calomel electrode was used as a reference electrode. The solution was heated at a constant temperature in a water bath at 50°C, and the stirring condition was 300 r / min. Constant voltage electrochemical deposition was performed, the deposition potential was 1.8 V, and the deposition time was 15 min. The obtained samples were then washed with deionized water in turn and dried in an oven at 50°C for 2 h.
[0065] (2) Take 200 mL of a mixed solution of 1 mol / L dilute sulfuric acid and 0.5 mol / L polyaniline, use the sample prepared in step (1) as the working electrode, the platinum electrode as the counter electrode, and the saturated calomel electrode as the reference electrode, and perform constant voltage electrochemical deposition at room temperature with a deposition potential of 0.75 V and a deposition time of 90 s to prepare the sample. Then, the obtained sample is washed with deionized water and anhydrous ethanol in turn, and dried in an oven at 50°C for 2 h to obtain a polyaniline / vanadium oxide / gold grid / PET composite positive electrode sheet with an area of 2.5 cm×2.5 cm.
[0066] Example 7
[0067] (1) 3.26 g of vanadyl sulfate was added to 200 mL of deionized water to prepare an electroplating solution, a gold grid / PET (2.5 cm×2.5 cm) was used as a working electrode, a platinum sheet was used as a counter electrode, and a saturated calomel electrode was used as a reference electrode. The solution was heated at a constant temperature in a water bath at 50°C, and the stirring condition was 300 r / min. Constant voltage electrochemical deposition was performed, the deposition potential was 1.8 V, and the deposition time was 15 min. The obtained samples were then washed with deionized water in turn and dried in an oven at 50°C for 2 h.
[0068] (2) Take 200 mL of a mixed solution of 1 mol / L dilute sulfuric acid and 0.5 mol / L polyaniline, use the sample prepared in step (1) as the working electrode, the platinum electrode as the counter electrode, and the saturated calomel electrode as the reference electrode, and perform constant voltage electrochemical deposition at room temperature with a deposition potential of 0.75 V and a deposition time of 120 s to prepare the sample. Then, the obtained sample is washed with deionized water and anhydrous ethanol in turn, and dried in an oven at 50°C for 2 h to obtain a polyaniline / vanadium oxide / gold grid / PET composite positive electrode sheet with an area of 2.5 cm×2.5 cm.
[0069] Comparative Example 1
[0070] 3.26g of vanadyl sulfate was added to 200mL of deionized water to prepare the electroplating solution. A gold grid / PET (2.5cm×2.5cm) was used as the working electrode, a platinum sheet was used as the counter electrode, and a water bath was heated at a constant temperature of 50°C. The stirring condition was 300r / min, and constant voltage electrochemical deposition was performed. The deposition potential was 1.8V and the deposition time was 15min. The obtained sample was then washed with deionized water and anhydrous ethanol in turn, and dried in an oven at 50°C for 2h. A vanadium oxide / gold grid / PET pole piece with an area of 2.5cm×2.5cm was obtained.
[0071] Comparative Example 2
[0072] Take 200mL of a mixed solution of 1mol / L dilute sulfuric acid and 0.5mol / L polyaniline, use gold grid / PET (2.5cm×2.5cm) as the working electrode, platinum electrode as the counter electrode, and saturated calomel electrode as the reference electrode, and prepare the sample by constant voltage electrochemical deposition at room temperature with a deposition potential of 0.75V and a deposition time of 60s. Then, the obtained sample is washed with deionized water and anhydrous ethanol in turn, and dried in an oven at 50°C for 2h to obtain a polyaniline / gold grid / PET electrode with an area of 2.5cm×2.5cm.
[0073] Comparative Example 3
[0074] (1) 3.26 g of vanadyl sulfate was added to 200 mL of deionized water to prepare the plating solution, and an ITO / PET current collector (2.5 cm×2.5 cm) was used as the working electrode, a platinum sheet was used as the counter electrode, and a saturated calomel electrode was used as the reference electrode. The solution was heated at a constant temperature in a water bath at 50°C, and the stirring condition was 300 r / min. Constant voltage electrochemical deposition was performed, and the deposition potential was 1.8 V and the deposition time was 15 min. The obtained samples were then washed with deionized water in turn and dried in an oven at 50°C for 2 h.
[0075] (2) Take 200 mL of a mixed solution of 1 mol / L dilute sulfuric acid and 0.5 mol / L polyaniline, use the sample prepared in step (1) as the working electrode, the platinum electrode as the counter electrode, and the saturated calomel electrode as the reference electrode, and perform constant voltage electrochemical deposition at room temperature with a deposition potential of 0.75 V and a deposition time of 60 s to prepare the sample. Then, the obtained sample is washed with deionized water and anhydrous ethanol in turn, and dried in an oven at 50°C for 2 h to obtain a polyaniline / vanadium oxide / ITO / PET composite positive electrode sheet with an area of 2.5 cm×2.5 cm.
[0076] Experimental testing
[0077] 1) Preparation of negative electrode sheets and battery assembly for flexible transparent aqueous zinc-ion batteries
[0078] 3g zinc sulfate, 3g sodium sulfate, 0.08g PEI solution and 0.5g boric acid were dissolved in 20mL deionized water to prepare the zinc negative electrode plating solution. A piece of zinc foil was used as the anode and a gold grid / PET (2.5cm×2.5cm) was used as the working electrode, and then electrodeposited at a constant voltage of -0.2V for 1h. The obtained sample was gently rinsed with deionized water and then dried in air for 2h to obtain a transparent zinc metal grid negative electrode sheet.
[0079] Conductive tapes were pasted on the edges of the transparent positive electrode and negative electrode to transmit electrons. A piece of PAM / ZnSO4 hydrogel electrolyte of appropriate size was sandwiched between the positive and negative electrodes, and the air was gently squeezed out. Then, the device was encapsulated as a whole with acrylic transparent tape to assemble a flexible transparent aqueous zinc ion battery. Figure 2 The effective working area of the flexible transparent aqueous zinc-ion battery is 4 cm 2 (2cm×2cm).
[0080] A flexible transparent aqueous zinc ion battery device was prepared according to the above flexible transparent aqueous zinc ion battery assembly process using the transparent zinc metal grid negative electrode sheet prepared by the above experimental process and the positive electrode sheet prepared by each embodiment and comparative example, and the performance test was carried out.
[0081] 2) Performance Testing
[0082] The transmittance of the prepared electrode and the assembled transparent aqueous zinc ion battery was tested by UV spectrophotometer. -2 Under a charge and discharge current of , the flexible transparent aqueous zinc ion battery device assembled with the positive electrode sheet prepared in Example 1 was subjected to a charge and discharge test, and a charge and discharge curve was obtained as shown in FIG. Figure 3 As shown in the figure, the battery charge and discharge voltage window is 0.2-1.5V, and the charge and discharge specific capacity is 22μAh·cm -2 The results show that the electrochemical performance of the battery is stable and the reversibility is good. At the same time, the batteries assembled with the pole pieces prepared in other embodiments and comparative examples were tested with the same parameters to obtain the discharge capacity data of each device. In addition, the assembled flexible transparent aqueous zinc ion battery device was tested at 100 μA·cm -2 The battery capacity retention rate was obtained by 200 cycles of charge and discharge current testing. The assembled flexible transparent aqueous zinc ion battery device was bent 500 times at a bending angle of 60° to obtain the discharge capacity retention rate of the battery after 500 cycles of 60° bending.
[0083] 3) Test result analysis
[0084] The test results are shown in Table 1:
[0085] Table 1 Performance data of batteries assembled from pole pieces prepared in various embodiments and comparative examples
[0086]
[0087] From Table 1 we can see that:
[0088] Comparing the samples of Example 1 and Comparative Example 1, in Comparative Example 1, only vanadium oxide was deposited on the gold grid. Due to the poor electrochemical stability of vanadium oxide, the capacity retention rate of the assembled battery after 200 cycles was only 51%; in Example 1, polyaniline was deposited for 60s on the basis of electrodeposition of vanadium oxide, which greatly improved the capacity retention rate to 71%, and the discharge specific capacity and bending resistance were also slightly improved. This shows that the introduction of polyaniline can significantly improve the electrochemical stability of the positive electrode.
[0089] Comparing the samples of Example 1 and Comparative Example 2, only polyaniline was deposited on the gold grid. Although the capacity retention rate of the sample assembled into a battery after 200 cycles reached 88%, its discharge specific capacity was only 5 μAh·cm -2 ; This shows that vanadium oxide can provide a higher specific capacity for batteries due to its good layered structure.
[0090] Comparing the samples of Example 1 and Comparative Example 3, the gold grid / PET substrate is replaced with ITO / PET in Comparative Example 3. Due to the uniform conductivity of the entire surface of ITO / PET, the transmittance of the prepared positive electrode plate and the assembled battery is low. In addition, when ITO / PET is used as an aqueous zinc ion positive electrode collector, an oxidation reaction will occur at a high potential, resulting in a decrease in its conductivity, thereby making the battery cycle retention rate as low as 32%; in addition, due to the poor mechanical properties of ITO, the bending resistance of the comparative example 3 sample after being assembled into a battery is very poor. After 500 cycles of 60° bending, the ITO layer broke, and the discharge capacity retention rate of the battery was as low as 15%; This shows that the gold grid / PET has the characteristics of a mesh morphology of the metal layer and a strong bonding force with the substrate, and gold also has good electrochemical stability. These characteristics help flexible transparent aqueous zinc ion batteries achieve high cycle stability, high transmittance and high bending resistance.
[0091] Compared with Example 2, Example 3 and Example 4, the deposition time of vanadium oxide in Example 1 is longer than that in Example 2, but shorter than that in Example 3 and Example 4; the discharge specific capacity ranking of the samples after assembling the battery is Example 2 < Example 1 < Example 3 < Example 4, and the transmittance ranking is just the opposite, Example 2 > Example 1 > Example 3 > Example 4; this shows that the deposition time of vanadium oxide mainly affects the battery discharge specific capacity and battery transmittance, the longer the deposition time, the more vanadium oxide is deposited, and therefore the higher the battery capacity, the higher the coverage of vanadium oxide on the electrode, which leads to lower transmittance, among which, due to the higher capacity contribution rate of vanadium oxide, its effect on the discharge specific capacity is more obvious.
[0092] Compared with Example 5, Example 6 and Example 7, the deposition time of polyaniline in Example 1 is longer than that in Example 5, but shorter than that in Example 6 and Example 7; the ranking of the cycle stability of the samples after assembling the battery is Example 5 < Example 1 < Example 6 < Example 7, and the ranking of the transmittance is Example 5 > Example 1 > Example 6 > Example 7; this shows that the deposition time of polyaniline mainly affects the battery cycle stability and transmittance, the longer the deposition time and the greater the deposition amount, the higher the battery cycle stability and the lower the transmittance.
[0093] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0094] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A method for preparing a flexible transparent aqueous zinc ion battery polyaniline / vanadium oxide composite positive electrode sheet, characterized in that: The following steps are involved: S1, using a vanadyl sulfate aqueous solution as an electroplating solution, using a gold grid / PET as a working electrode, and a platinum sheet as a counter electrode to construct a two-electrode structure, and using a constant voltage electrochemical deposition method to deposit a vanadium oxide layer on the surface of the gold grid / PET to prepare vanadium oxide / gold grid / PET; S2, adding sulfuric acid and aniline into deionized water to prepare an electroplating solution, constructing a three-electrode structure with vanadium oxide / gold grid / PET as a working electrode, a platinum electrode as a counter electrode, and a saturated calomel electrode as a reference electrode, and using a constant voltage electrochemical deposition method to deposit a polyaniline layer on the surface of vanadium oxide / gold grid / PET to obtain a composite positive electrode sheet.
2. The method for preparing the flexible transparent aqueous zinc ion battery polyaniline / vanadium oxide composite positive electrode sheet according to claim 1, characterized in that: The sheet resistance of the gold grid / PET current collector is 1-2Ω / sq, and the light transmittance is 80-90%.
3. The method for preparing the flexible transparent aqueous zinc ion battery polyaniline / vanadium oxide composite positive electrode sheet according to claim 1, characterized in that: The concentration of the vanadyl sulfate aqueous solution is 0.05-0.2 mol / L.
4. The method for preparing the flexible transparent aqueous zinc ion battery polyaniline / vanadium oxide composite positive electrode sheet according to claim 1, characterized in that: In S1, during the electrochemical deposition process, the two-electrode system is stirred at a constant temperature of 50-80°C and a stirring condition of 300r / min-1000r / min.
5. The method for preparing a flexible transparent aqueous zinc ion battery polyaniline / vanadium oxide composite positive electrode sheet according to claim 1 or 4, characterized in that: In S1, the deposition potential range of the constant voltage electrochemical deposition method is 0.8-2.0 V, and the deposition time is 10-25 min.
6. The method for preparing the flexible transparent aqueous zinc ion battery polyaniline / vanadium oxide composite positive electrode sheet according to claim 1, characterized in that: In S2, in the prepared electroplating solution, the concentration of sulfuric acid is 0.5-2 mol / L, and the concentration of aniline is 0.2-1 mol / L.
7. The method for preparing the flexible transparent aqueous zinc ion battery polyaniline / vanadium oxide composite positive electrode sheet according to claim 1, characterized in that: In S2, the deposition potential range of the constant voltage electrochemical deposition method is 0.55-0.95 V, and the deposition time is 30-120 s.
8. Flexible transparent aqueous zinc ion battery polyaniline / vanadium oxide composite positive electrode plate, characterized in that: The method is prepared by any one of claims 1 to 7.
9. Use of the flexible transparent aqueous zinc ion battery polyaniline / vanadium oxide composite positive electrode sheet according to claim 8 in the preparation of aqueous zinc ion batteries.
10. An aqueous zinc ion battery, characterized in that: It comprises the flexible transparent aqueous zinc ion battery polyaniline / vanadium oxide composite positive electrode plate as described in claim 8.
Citation Information
Patent Citations
Flexible water system zinc ion battery
CN110190344A
Large-scale continuous preparation method of flexible integrated water system energy storage device
CN112909313A
Vanadium oxide electrode material with nanorod structure, and preparation method and application thereof
CN113223865A
Preparation method and application of polyaniline-coated ferric vanadate flexible electrode
CN114464764A
Preparation method of homogeneous manganese dioxide / polyaniline zinc ion battery positive electrode material
CN117012946A